Fungicide management in the Asian soybean rust - Viegas Neto, Antonio Luiz; Márcio Alves de Souza, Cristiano; Fernandes Bertoncello, Bruno; dos Santos Lima Júnior, Izidro; Maria Maraschi da Silva Piletti, Ligia; Roberto Rigotte, Márcio (Revista Agrogeoambiental, 2021)
Asian soybean rust is the major crop disease and the management of the use of the fungicide is important for effective control. The objective of this work was to evaluate the management of fungicides with sequential applications to control Asian soybean rust. The experimental design used was a randomized block with four replications and eight treatments with different combinations of fungicides from the following chemical groups: triazole, strobilurin, carboxamide, and dithiocarbamate. The applications were carried out with backpack spray equipment at constant pressure (CO2) and a spray rate of 200 L ha-1. The severity of rust, the area under the disease progress curve, control efficiency, mass of 1,000 grains, and productivity were evaluated. The protective fungicide mancozeb, in mixtures with systemic fungicides, were more effective for the control of Asian soybean rust than the systemic fungicides applied without the protective fungicide.